Analisis rantai pasok bahan baku utama ayam pada rice bowl di UKM Tahu Baso Miwiti - Tsani, Muhammad Al Farabi; Manurung, Pebrika; Amanda, Della; Veronika, Relita Imelda; Farhan, Edrian Arizal (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
This study aims to determine the analysis of the chicken raw material supply chain at the Rice Bowl at Miwiti SMEs using a qualitative descriptive approach method based on the results of interviews and direct observations at the Miwiti SME location. The results of the study indicate that the supply chain at the Rice Bowl at Miwiti SMEs cannot be separated from the Upstream supply chain, Internal supply chain, and Downstream supply chain. These results indicate that the upstream supply chain is related to the activity of supplying raw materials starting from chicken traders at Pasar Anyar Bogor - processing into chicken rice bowls - rice bowls at Miwiti SMEs. The internal supply chain includes procurement of raw materials - washing - cutting - draining water - seasoning - frying - draining oil - packaging. The downstream supply chain includes distribution activities to end consumers. The supply chain that occurs at Miwiti SMEs is running well from the procurement of chicken raw materials from suppliers to customers.